Changes in Metabolic Regulation and the Microbiota Composition after Supplementation with Different Fatty Acids in db/db Mice - Beatriz Elina Martínez-Carrillo; Talia Mondragón-Velásquez; Ninfa Ramírez-Durán; José Félix Aguirre-Garrido; Roxana Valdés-Ramos; Ana Laura Guadarrama-López; Arturo Castillo-Cardiel (International Journal of Food Science)
Introduction. The effects of fatty acids on health vary and depend on the type, amount, and route of consumption. EPA and DHA have a defined role in health, unlike coconut oil. Objective. The aim was to investigate the changes in metabolic regulation and the composition of the culture-dependent microbiota after supplementation with different fatty acids in db/db mice. Material and Methods. We were using 32 8-week-old db/db mice, supplemented for eight weeks with EPA/DHA derived from microalgae as well as coconut oil. The lipid, hormonal profiles, and composition of the culture-dependent microbiota and the phylogenetic analysis based on the 16S rRNA gene sequencing were determined for identification of the intestinal microbiota. Results. Enriched diet with EPA/DHA reduced TNF-α, C-peptide, insulin resistance, resistin, and the plasma atherogenic index, but increased TC, LDL-c, VLDL-c, and TG without changes in HDL-c. Coconut oil raised the HDL-c, GIP, and TNF-α, with TG, insulin resistance, adiponectin, and C-peptide reduced. Conclusion. The most abundant microbial populations were Firmicutes and the least Proteobacteria. EPA/DHA derived from microalgae contributes to improving the systemic inflammatory status, but depressed the diversity of the small intestine microbiota. Coconut oil only decreased the C-peptide, raising TNF-α, with an unfavorable hormonal and lipid profile.